Prediksi Pencapaian Target Peserta Keluarga Berencana Pasca Persalinan menggunakan Algoritma Backpropagation - Stefani Hardiyanti Putri; Gunadi Widi Nurcahyo; Y Yuhandri (Jurnal Sistim Informasi dan Teknologi, 2021)
Population growth in Indonesia continues to increase, so the government makes a program to control the rate of growth of the population, namely the Family Planning Program (KB). The implementation of family planning also has another objective, namely to reduce the risk of maternal death after childbirth. To measure the level of increasing target achievement of postpartum family planning participants. So that it can be a reference for the DPPKBP3A in carrying out the postpartum family planning program. Data from the Population Control, Family Planning, Women Empowerment and Child Protection (DPPKBP3A) District Lima Puluh Kota data processed in this study is data on the achievement of postpartum family planning participants from 2018 to 2020. Data processing uses the Backpropagation algorithm through several stages, namely the stage initialization, activation stage, weight training (weight change) and iteration stage. One of the results obtained from the calculation is the comparison of the target with the output gradient error in Suliki District in 2018, namely the target of 0.11311 and the result of the error gradient output is -0.1171. The prediction results obtained from this process become a reference for the Population Control, Family Planning and Women Empowerment and Child Protection Agency (DPPKBP3A) of District Lima Puluh Kota to implement the implementation of postpartum family planning programs to the community the following year.